Nanostructured hollow tubes based on chitosan and alginate multilayers - Silva, Joana M. (2014)
The design and production of structures with nanometer-sized polymer ﬁ lms based on layer-by-layer (LbL) are of particular interest for tissue engineering since they allow the precise control of physical and biochemical cues of implantable devices. In this work, a method is developed for the preparation of nanostructured hollow multilayers tubes combining LbL and template leaching. The aim is to produce hollow tubes based on polyelectrolyte multilayer ﬁ lms with tuned physical-chemical properties and study their effects on cell behavior. The ﬁnal tubular structures are characterized by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), microscopy, swelling, and mechanical tests, including dynamic mechanical analysis (DMA) in physiological simulated conditions. It is found that more robust ﬁlms could be produced upon chemical cross-linking with genipin. In particular, the mechanical properties conﬁ rms the viscoelastic properties and a storage and young modulus about two times higher. The water uptake decreases from about 390% to 110% after the cross-linking. The biological performance is assessed in terms of cell adhesion, viability, and proliferation. The results obtained with the cross-linked tubes demonstrate that these are more suitable structures for cell adhesion and spreading. The results suggest the potential of these structures to boost the development of innovative tubular structures for tissue engineering approaches.